PRUDENCE ACCOUNTING, LEVERAGE, AND FIRM VALUE: THE PERSPECTIVE SIGNALING THEORY - Rizka Novika Isyauqina; Imam Nurcahyo Fambudi (Transpublika Publisher, 2024)
The firm has a long-term goal of optimizing the value because it is related to the share price so as to maximize the prosperity of shareholders. This study aims to determine and analyze the effect of prudence and leverage on firm value (Empirical Study of Public Companies in Indonesia). This study has a novelty in the measurement of prudence developed by Fambudi et al using the Heckit Model. The population of this study were all public companies in Indonesia during 2017-2021. A total of 332 companies were selected as samples using a purposive sampling technique, with secondary data utilized for the analysis. The results of this study indicate that prudence has a significant positive effect on firm value. Companies that apply prudence are often seen as careful and responsible entities. This good reputation builds investor and creditor confidence. Meanwhile, leverage has a significant negative effect on firm value. A high leverage ratio indicates that the company has a large debt and tends to be riskier. This study includes two control variables: firm size and growth opportunities. Firm size, as a control variable, has a negative effect on firm value, while company growth has a significant positive effect on firm value.